ANALISIS FAKTOR PSIKOLOGIS PENGGUNA BATU AKIK DI KOTA MALANG - Rizki Kurniawan (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aims to analysis of the psychological factors the gemstone user in Malang. The research is a qualitative descriptive with phenomenology approach. This approach was chosen because the researchers wanted to examine more about the common experiences of informants while using gemstone. This study uses (6) informant obtained using the snowball of gemstone users who live in Malang. Data collection techniques used is the direct observation, interviews and documentation. Data analysis techniques includes: preparing and reading data,  recode,  describe  coding,  narrating  themes  and interpret  the  data.  The results of studies obtained the following findings. (1) informant has the motivated encouragement  external, motivation  individual  motifs  and  motivation  needs jewelry in using gemstone. (2) the user's perception of gemstone have the notion that by using gemstone one's confidence will increase. (3) learning classified into stimulation  impulse  (drive)  and  the  stimulation signal  (cue)  in  the  use  of gemstone. (4) beliefs and attitudes based on three categories: knowledge, feelings and evaluation of the use of gemstone.Keywords: psychological factors, motivation, perception, learning, beliefs and attitudes, phenomenology